-x+4>-3x-4
+x +x
---------------------
4>-3x-4
+4 +4
----------------
8>-3x
/3 /3
----------------
8>2.7
x=2.7
Hope it helped!
Answer:
x = -4
Step-by-step explanation:
Plug in -4 into the function and solve for x:
f(x) = 6x + 20
-4 = 6x + 20
-24 = 6x
-4 = x
So, the answer is x = -4
9514 1404 393
Answer:
22
Step-by-step explanation:
The average of the 6 even integers is the odd integer halfway between the first three and the last three. That average value is 126/6 = 21, so the 4th integer is 21+1 = 22.
_____
All 6 are {16, 18, 20, 22, 24, 26}.
Answer:
D = 11
Step-by-step explanation:
A = 4
B = 9
C = 11
D = 4 + (2 * 9) - 11
D = 4 + 18 - 11
D = 22 - 11
D = 11
brainliest plz